2014
DOI: 10.1111/dmcn.12513
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological abnormalities in the sensorimotor cortices during the motor planning and movement execution stages of children with cerebral palsy

Abstract: AIM This investigation used magnetoencephalography (MEG) to examine the neural oscillatory responses of the sensorimotor cortices during the motor planning and movement execution stages of children with typical development and children with cerebral palsy (CP). METHOD The study involved 13 children with CP (nine males, four females; mean [SD] age 14y 3mo [9mo], range 10–18y; height 1.61m [0.08m]; weight 52.65kg [13kg]), and 13 age- and sex-matched children with typical development (height 1.64m [0.06m]; weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 25 publications
(81 reference statements)
5
75
3
2
Order By: Relevance
“…29 Grip strength and motor coordination was slightly impaired in prenatal ischemic rats 42 while mild locomotor disturbances were significant only in male rats. 40 Prenatal hypoxia delayed the development of motor skills and impaired motor learning in rats 43 while prepulse inhibition was impaired in adult prenatal ischemic guinea pigs, suggestive of abnormal somatosensory gating.…”
Section: Prenatal Ischemia In Animal Models Of Wmimentioning
confidence: 96%
See 1 more Smart Citation
“…29 Grip strength and motor coordination was slightly impaired in prenatal ischemic rats 42 while mild locomotor disturbances were significant only in male rats. 40 Prenatal hypoxia delayed the development of motor skills and impaired motor learning in rats 43 while prepulse inhibition was impaired in adult prenatal ischemic guinea pigs, suggestive of abnormal somatosensory gating.…”
Section: Prenatal Ischemia In Animal Models Of Wmimentioning
confidence: 96%
“…36,40,43 Several studies have shown that abnormal processing and integration of afferent information in the somatosensory cortex is sufficient to drive disturbances in motor planning and execution. 20,23,29 Somatosensory map disorganization in prenatal ischemic rats may lead to abnormal development of locomotion patterns, which in turn feed the somatosensory cortex with aberrant somatosensory inputs, thus increasing the degradation of map topography and neuronal properties in the somatosensory cortex through a vicious cycle.…”
Section: Prenatal Ischemia In Animal Models Of Wmimentioning
confidence: 99%
“…75 Another study that used MEG reported abnormal beta-wave activity in children with spastic hemipar esis during the planning stage of a knee extension task. 76 This finding suggested that motor planning, rather than muscular recruitment, might have been the limiting factor in the controlled execution of the motor task. If similar impairments are found to occur commonly in UCP, an increased therapeutic focus on motor planning and sensorimotor co-ordination, rather than motor output, might accelerate rehabilitation or improve its effectiveness in people with this condition.…”
Section: Diffusion Mri and Thalamocortical Pathwaysmentioning
confidence: 99%
“…Further, a multitude of studies examining the neurophysiology of movement disorders, such as Parkinson’s disease (Brown, 2007; Cassidy et al, 2002; Heinrichs-Graham et al, 2014a; Heinrichs-Graham et al, 2014b; Little and Brown, 2014; Pollok et al, 2012; Weinberger et al, 2006), cerebral palsy (Kurz et al, 2014), Tourette syndrome (Franzkowiak et al, 2010; Niccolai et al, 2015; Tinaz et al, 2014), dystonia (Hinkley et al, 2012), and stroke (Rossiter et al, 2014a; Shiner et al, 2015; Wilson et al, 2011a) have shown aberrant sensorimotor beta power at rest and/or during movement. These beta aberrations are often correlated with symptom severity, which suggests that the degree of motor impairment is closely tied to beta activity in the motor cortices.…”
Section: Introductionmentioning
confidence: 99%